2023
DOI: 10.3390/jcm12175543
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease in Obesity: Bariatric Surgery as Both the Cause and the Cure in the Morbidly Obese Population

Muaaz Masood,
Donald Low,
Shanley B. Deal
et al.

Abstract: Gastrointestinal reflux disease (GERD) is a chronic, highly prevalent condition in the United States. GERD can significantly impact quality of life and lead to complications including aspiration pneumonia, esophageal stricture, Barrett’s esophagus (BE) and esophageal cancer. Obesity is a risk factor for GERD, which often improves with weight loss and bariatric surgery. Though the incidence of bariatric surgery, in particular, minimally invasive sleeve gastrectomy, has risen in recent years, emerging data has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 151 publications
0
3
0
Order By: Relevance
“…A comprehensive, stepwise approach to the management and treatment of GERD following SG has recently been published by Masood et al [ 45 ]. Lifestyle modifications are initially recommended following SG as part of a comprehensive bariatric surgery center’s pre- and postoperative education and long-term follow-up plan with patients.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive, stepwise approach to the management and treatment of GERD following SG has recently been published by Masood et al [ 45 ]. Lifestyle modifications are initially recommended following SG as part of a comprehensive bariatric surgery center’s pre- and postoperative education and long-term follow-up plan with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, GERD has great importance as it strongly affects quality of life (12,36) and incurs costs related to long-term use of medications, with potential sideeffects (37) and the need for additional revisional surgeries (38). Recent reports have demonstrated that among gastric bypasses, OAGB may be associated not only with biliary reflux but also with acid reflux (39), and RYGB, even if it is the gold standard procedure to treat associated obesity and GERD, is associated with a non-negligible rate of long-term reflux (12,16,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…GERD typically manifests as heartburn and regurgitation, although atypical symptoms (i.e., cough, laryngitis, asthma, or chest pain) may be present in some patients. Masood et al details the current management and treatment paradigms of post-SG GERD in a recently published review [124]. Endoscopy may be performed as part of a diagnostic work-up, which can also include esophagram, esophageal manometry, and pH testing, for further anatomical and physiological eval-uation in selected patients presenting with GERD.…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%